Effect of silymarin alcoholic extract on surgery‐induced intraperitoneal adhesion in rats. Issue 1 (17th January 2016) - Karimi, Mehrdad; Parsaei, Pouya; Shafiei‐Alavijeh, Soheil; Rafieian‐Kopaei, Mahmoud; Asadi, S. Yazdan
Abstract : Aim: Adhesion formation is the greatest complication in abdominal surgery. S ilybum marianum ( S . marianum ) extract contains phenolic compounds whit antioxidant activities, thus could reduce adhesion formation. The aim of the present study was to examine its effect on intraabdominal adhesion. Patients and Methods: Thirty male Wistar rats were randomly divided into three groups. Groups A and B received 1 per cent and 5 per cent concentrations of the S . marianum extract, and group C (control group) received distilled water. After anaesthesia was administered, the abdominal wall was opened and three shallow, longitudinal and transverse incisions (2 cm in length) were made on the right wall of the abdomen. A 2 × 2 cm piece was removed from the peritoneal surface on the left side of the abdominal wall; 3 mL of S . marianum extract or distilled water was then administered into the abdominal cavity. Adhesion degrees were determined according to the Canbaz scale. Histopathological examination was also determined according to the severity of fibrosis and inflammation. Data analysis was performed using SPSS version16. Results: There was significant difference in the adhesion formation between the groups ( P = 0.023). The adhesion degree in groups A and B were significantly lower than that of the control ( P < 0.05). In the histopathological examination, significant differences were observed between the control and extract‐treated groups in term of fibrosis and inflammation ( P < 0.05). Conclusion: S . marianum extract has preventive effects on post‐laparotomy intraabdominal adhesion. Therefore, through further clinical studies, S . marianum extract and its derived compounds might be used in humans for the treatment of these complications.